Inovasi Media Ajar Berbasis Video pada Materi Pembangkit Listrik Tenaga Panas Bumi (PLTPB) sebagai Upaya Penguatan Pemahaman Konsep Mahasiswa - Bilal Bara Saputra; Malika Azizah Faradillah; Aghna Athaillah Al Fawwaz; Ravianri Putra Dinata; Yoga Angga Pratama; Didik Aribowo (Prosiding Seminar Nasional Ilmu Pendidikan, 2026)
Geothermal Power Plant (PLTP) subject matter is characterized by its highly technical nature, involving thermodynamic cycles, mechanical systems, and energy conversion processes that pose significant comprehension challenges when taught through traditional classroom methods. To bridge this gap, this study developed video-based instructional media using the ADDIE model framework (Analysis, Design, Development, Implementation, Evaluation) within a Research and Development (R&D) paradigm. The systematic development process began with identifying learning gaps and mapping instructional content, followed by creating a structured video script, producing the media, conducting audience trials, and carrying out a feedback-based evaluation cycle. Evidence gathered from the study confirms that the produced media fulfilled validity, practicality, and effectiveness criteria in fostering students' conceptual mastery of geothermal electricity generation. Combining motion graphics, narration, and on-screen text enabled learners to engage meaningfully with technical components including turbines, condensers, cooling towers, and synchronous generators. The ADDIE-based video media is therefore recommended as a reliable instructional resource for teaching the principles and operational dynamics of Geothermal Power Plants.